Music from Apartment 8 : New and Selected Poems - Stone, John, 1936-2008 (Book collections on Project MUSE., 2004)
Poet and cardiologist John Stone is a man of many voices. A gifted verse maker, he exhibits in his writing the qualities of a compassionate physician, a musician, linguist, naturalist, and down-to-earth yet whimsical grandfather, son, husband, and brother. Selections from four previous books together with twenty-two new works compose this exquisite volume, a 'best of the best' sampling from a beloved poet.